Perspectives of hospital emergency department staff on trauma‐informed care for injured children: An Australian and New Zealand analysis. (6th August 2017) - Hoysted, Claire; Babl, Franz E; Kassam‐Adams, Nancy; Landolt, Markus A; Jobson, Laura; Curtis, Sarah; Kharbanda, Anupam B; Lyttle, Mark D; Parri, Niccolò; Stanley, Rachel; Alisic, Eva
Abstract : Aim: To examine Australian and New Zealand emergency department (ED) staff's training, knowledge and confidence regarding trauma‐informed care for children after trauma, and barriers to implementation. Methods: ED staff's perspectives on trauma‐informed care were assessed using a web‐based self‐report questionnaire. Participants included 468 ED staff (375 nursing and 111 medical staff) from hospitals in Australia and New Zealand. Data analyses included descriptive statistics, χ 2 tests and multiple regressions. Results: Over 90% of respondents had not received training in trauma‐informed care and almost all respondents (94%) wanted training in this area. While knowledge was associated with a respondent's previous training and profession, confidence was associated with the respondent's previous training, experience level and workplace. Dominant barriers to the implementation of trauma‐informed care were lack of time and lack of training. Conclusions: There is a need and desire for training and education of Australian and New Zealand ED staff in trauma‐informed care. This study demonstrates that experience alone is not sufficient for the development of knowledge of paediatric traumatic stress reactions and trauma‐informed care practices. Existing education materials could be adapted for use in the ED and to accommodate the training preferences of Australian and New Zealand ED staff.